Nutrient addition affects scaling relationship of leaf nitrogen to phosphorus in Arabidopsis thaliana. (12th October 2018) - Yan, Zhengbing; Li, Xiuping; Tian, Di; Han, Wenxuan; Hou, Xinghui; Shen, Haihua; Guo, Yalong; Fang, Jingyun
Abstract : Plain Language Summary Abstract: Ambient nutrient changes influence the coupling of nitrogen (N) and phosphorus (P) in terrestrial ecosystems, but whether it could alter the scaling relationship of plant leaf N to P concentrations remains unclear. Here, we conducted experimental manipulations using Arabidopsis thaliana, with five levels of N and P additions and nine repeated experiments, and then evaluated the changes in the scaling relationship of leaf N to P concentrations under nutrient additions. Overall, leaf N concentration scaled as 0.552 power of leaf P concentration for all data pooled. However, when considering the effect of the type of nutrient addition, the scaling relationship for pooled data of the five levels of N addition was insignificant at two growth stages (young‐leaf and mature‐leaf stages), whereas the scaling relationship for pooled data of the five levels of P addition was significant with exponents of 0.290 and 0.268 at the two growth stages, respectively. Furthermore, the scaling exponent decreased with the increasing levels of N addition, but increased with the increasing levels of P addition. This suggests that high nutrient availability decreases the variability in its own concentration, but promotes the fluctuation in another tightly associated nutrient concentration in leaves among plant individuals. We call this as Nutrient Availability–Individual Variability Hypothesis. Our results suggest that scaling relationship of leaf N to P concentrations is largely modulated by the type and level of nutrient addition, and analyses of leaf N vs. P scaling relationships using pooled data could lose much information rooted in biologically and ecologically significant variances. These findings provide important implications for the parameterization in modelling stoichiometric growth and nutrient cycles in terrestrial ecosystems, and for understanding population structures, processes and functioning under varying nutrient environments. However, whether our observed patterns in A. thaliana could be extended to those at community level warrants further studies and more validations. Aplain language summary is available for this article.